Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd004479.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Simple aspiration versus intercostal tube drainage for primary spontaneous pneumothorax in adults

Abstract: There is no significant difference between simple aspiration and intercostal tube drainage with regard to: immediate success rate, early failure rate, duration of hospitalisation, one year success rate and number of patients requiring pleurodesis at one year. Simple aspiration is associated with a reduction in the per cent of patients hospitalized when compared with intercostal tube drainage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 34 publications
0
23
0
3
Order By: Relevance
“…Although blinding was not secured in all studies considering the characteristics of the offered treatment, we believe that it probably did not lead to performance bias or detection bias. Among the three previous systematic reviews on the same topic, the study by Wakai et al[10] assessed only the risk of bias regarding randomisation and blinding, and other studies used other tools for assessment [9,11]. Thus, comparing their results with ours was not fully applicable.…”
Section: Discussionmentioning
confidence: 84%
“…Although blinding was not secured in all studies considering the characteristics of the offered treatment, we believe that it probably did not lead to performance bias or detection bias. Among the three previous systematic reviews on the same topic, the study by Wakai et al[10] assessed only the risk of bias regarding randomisation and blinding, and other studies used other tools for assessment [9,11]. Thus, comparing their results with ours was not fully applicable.…”
Section: Discussionmentioning
confidence: 84%
“…A recent evidence-based medicine (EBM) review found no significant difference between simple aspiration and intercostal tube drainage with regard to immediate success rate, early failure rate, duration of hospitalization, one-year success rate, and number of patients requiring pleurodesis at one year. Simple aspiration does not require hospitalization, compared with intercostal tube drainage (Wakai et al, 2007;Zehtabchi and Rios, 2008).…”
Section: Diagnostic Approaches To Pspmentioning
confidence: 99%
“…Various thoracostomy techniques by pneumothorax size are introduced in recent studies 17-19. However, we used single size tube in order to exclude decompression pressure variation by diameter of pleural opening.…”
Section: Discussionmentioning
confidence: 99%